1995
DOI: 10.1111/j.1468-2958.1995.tb00364.x
|View full text |Cite
|
Sign up to set email alerts
|

Communicating Intentions Through Nonverbal Behaviors Conscious and Nonconscious Encoding of Liking

Abstract: Thefundamental components of interpersonal transactions at the nonverbal level ofen include the cognitively held intention of one person to increase or decrease affiliation with his or her partner, the encoding of this intention into behavioral displays, and the decoding of the behavioral displays by the other Nonverbal encoding of relational information may be conducted at less than conscious levels of infirmation processing although intentions may be held consciously. A study was conducted in which naive con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(37 citation statements)
references
References 61 publications
0
36
0
1
Order By: Relevance
“…One study even found that confederates who were instructed to create liking with a partner could not identify accurately the behaviors they used and how they used them, even though they were successful at their goal (Palmer & Simmons, 1995). Research on nonconscious behavioral mimicry (reviewed in the Rapport section below) has also demonstrated that people are not consciously aware that they mimic the behaviors of others or that other people might be mimicking their behaviors or that this mimicry creates liking Chartrand, Maddux, & Lakin, 2005).…”
Section: Social Relationshipsmentioning
confidence: 99%
“…One study even found that confederates who were instructed to create liking with a partner could not identify accurately the behaviors they used and how they used them, even though they were successful at their goal (Palmer & Simmons, 1995). Research on nonconscious behavioral mimicry (reviewed in the Rapport section below) has also demonstrated that people are not consciously aware that they mimic the behaviors of others or that other people might be mimicking their behaviors or that this mimicry creates liking Chartrand, Maddux, & Lakin, 2005).…”
Section: Social Relationshipsmentioning
confidence: 99%
“…When enacting the disliking condition, confederates were given the opposite instructions: to avoid smiling and eye contact, to sit far away from Ps, to lean away from Ps, and to avoid matching Ps' posture. These nonverbal behaviors are those commonly used to communicate liking and affection, or the lack thereof (Burgoon & Le Poire, 1999;Palmer & Simmons, 1995).…”
mentioning
confidence: 99%
“…To ensure that they were not familiar with each other prior to their participation, Persons A and B completed two measures of prefamiliarity adapted from a study by Palmer and Simmons (1995 ranged from 1 (not at all) to 7 (very well). The second question was "How would you describe your relationship with this person?'…”
Section: Methodsmentioning
confidence: 99%